Venetoclax responses of pediatric ALL xenografts reveal sensitivity of MLL-rearranged leukemia - Khaw, Seong Lin; Suryani, Santi; Evans, Kathryn; Richmond, Jennifer; Robbins, Alissa; Kurmasheva, Raushan T.; Billups, Catherine A.; Erickson, Stephen W.; Guo, Yuelong; Houghton, Peter J.; Smith, Malcolm A.; Carol, Hernan; et al. (Blood, 2016)
The clinical success of the BCL-2-selective BH3-mimetic venetoclax in patients with poor prognosis chronic lymphocytic leukemia (CLL) highlights the potential of targeting the BCL-2-regulated apoptotic pathway in previously untreatable lymphoid malignancies. By selectively inhibiting BCL-2, venetoclax circumvents the dose-limiting, BCL-XL-mediated thrombocytopenia of its less selective predecessor navitoclax, while enhancing efficacy in CLL. We have previously reported the potent sensitivity of many high-risk childhood acute lymphoblastic leukemia (ALL) xenografts to navitoclax. Given the superior tolerability of venetoclax, here we have investigated its efficacy in childhood ALL. We demonstrate that in contrast to the clear dependence of CLL on BCL-2 alone, effective antileukemic activity in the majority of ALL xenografts requires concurrent inhibition of both BCL-2 and BCL-XL. We identify BCL-XL expression as a key predictor of poor response to venetoclax and demonstrate that concurrent inhibition of both BCL-2 and BCL-XL results in synergistic killing in the majority of ALL xenografts. A notable exception is mixed lineage leukemia–rearranged infant ALL, where venetoclax largely recapitulates the activity of navitoclax, identifying this subgroup of patients as potential candidates for clinical trials of venetoclax in childhood ALL. Conversely, our findings provide a clear basis for progressing navitoclax into trials ahead of venetoclax in other subgroups. •Venetoclax demonstrates potent in vitro and in vivo single-agent activity in MLL-rearranged ALL xenografts.•Clinically efficacious BH3-mimetic therapy for other high-risk ALL subtypes is likely to require concurrent BCL-2 and BCL-XL inhibition.